PENGARUH APLIKASI SUBSTRAT IKAN TERI PADA PERMUKAAN EMAIL TERHADAP REMINERALISASI EMAIL - Harun A. Gunawan (Faculty of Dentistry, Universitas Indonesia, 2015)
Topical fluoridation recently has become the method of choice in caries prevention. Fluoride plays an important role not only in the formation of fluoroapatite, but also promoting enamel remineralization. Enamel remineralization occur when the enamel environment supersaturated with calcium and phosphate ions. When the pH level decrease, the rise of H+ ions, the hydroxyl of the apatite will be drawn out from the enamel, and substitute by fluoride ions, this condition will cause apatite breakdown, and both calcium and phosphate will be released to the enamel environment. The release of those minerals will cause supersaturation and promoting enamel remineralization. In the nature fluoride can be found in the sea fishes, such like teri (anchovy, Stolephora sp) fishes. Teri fish has about 17 - 38 ppm of fluoride content. The high fluoride content of teri fish, lead this research to knwo the influence of its application to the enamel surface on remineralization process, measured with enamel surfacce roughness and hardness tests. Seven enamel discs, 5x10 mm (W and L) obtained from 4 impacted third molars, were used in this research. One disc used as initial control, and 6 discs divided into 2 groups, used as experiment groups. All of the experimental discs, demineralized using 50% phosphoric acid, then 3 of them were applied with teri substrate, whether other 3 discs applied with non ionic aquadest. All experimental discs, then immersed in the remineralization solution containing calcium phosphate stabilized with caseinphosphopeptide. The cycle above repeated for 26 times. Analysis of the specimens were done using surfcom for enamel rougness and Buehler microhardness tester for surface hardness. Surfaace roughness of the group is 1,78 μm compared to the initial group (215 μm), and enamel surface micro hardness of the group is (376 VHN), significantly differ from the control group, 358 VHN. Conclusion: based on this research result, it can be concluded that : Teri fish substrate application on enamel surface causes enhancement of enamel remineralisation, as evaluated by surface roughness and micro hardness.